THE DEVELOPMENT MODEL OF STUDENTSâ GUIDANCE MANAGEMENT BASED ON ISLAMIC ACADEMIC CULTURE IN UNISSULA - -, Nuridin (The Journal of Educational Development, 2014)
Sultan Agung Islamic University (UNISSULA) has formulated a vision to be the leading Islamic University in building the best generation (khaira ummah), developed science and teechnology on the basis of Islamic values and Islamic civilization toward a prosperous community blessed by Allah (Statute UNISSULA, 2011). Therefore, UNISSULA has applied Islamic Academik Culture as the implementation to studentsâchoaching which creates the best generation. This study is aimed to develop the model studentsâguidence management based on Islamic Academic Culture. This study was designed using the research approach an development (R and D). The data collection was done by; firts, a qualitative phase approach that includes interviews, observations, documentation and questionaires. Second, the literature review was done by assessing the stage of grand theory. Third, the stage of development of hypothetical models in which the data collection used Focus Group Discussion (FGD). The fourth was the model evaluation phase, empirically the researcher conducted field trials. After perfecting the conceptual model which has been validated by expert, the conceltual models were tested. For the data analysis, the researcher used qualitative data analysis, and data validity checking techniques. Products developed and validated in the research of developing the model of studentsâguidance based on Islamic Academic Culture is the guidelines of studentsâchoaching management which include: (1) Guidelines for studentsâchoaching planning, (2) Guidelines for organizing student development, (3) Guidelines for the implementation of studentsâchoaching, and (4) Guidelines for monitoring studentsâchoaching.